2015
DOI: 10.1016/j.copsyc.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Using theory to develop and test interventions to promote changes in health behaviour: evidence, issues, and recommendations

Abstract: Using theory to develop health behaviour interventions provides a useful framework to accumulate evidence and has been associated with larger changes in health behaviour. The present review suggests, however, that the evidence that using theory in this way produces greater health behaviour change is mixed. Furthermore, evaluating such evidence is difficult because: (i) a significant proportion of interventions are not based on theory; (ii) those that are, tend not to apply the theory extensively; (iii) theory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(153 citation statements)
references
References 65 publications
3
148
1
1
Order By: Relevance
“…Specifically, the present findings point to the importance of using theory to inform the design of interventions (Michie, Webb, & Sniehotta, 2010;Prestwich, Webb, & Conner, 2015) and involving family members (e.g. mothers) in such programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the present findings point to the importance of using theory to inform the design of interventions (Michie, Webb, & Sniehotta, 2010;Prestwich, Webb, & Conner, 2015) and involving family members (e.g. mothers) in such programmes.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that health behaviour interventions that are based on theory are more effective than those that are not (Prestwich, Webb, & Conner, 2015;Webb, Joseph, Yardley & Michie, 2010), although other reviews have concluded that they produce similar sized effects (Prestwich et al, 2014a). However, many so-called theory-based interventions are probably better classified as "theory-inspired" rather than "theory-based" (Hardeman et al, 2002;Michie & Abraham, 2004).…”
Section: Effectiveness Of Interventions To Change Health Behavioursmentioning
confidence: 99%
“…Relatedly, using theory to develop health behaviour interventions has been advocated by some (Prestwich et al, 2017) as it provides a useful framework for identifying the key modifiable determinants of health behaviour, designing interventions to target these determinants and accumulating evidence. Some reviews have reported that the use of theory is associated with larger changes in health behaviour (Prestwich et al, 2015), although other reviews have concluded that theory-based interventions and interventions that do not use theory produce similar effect sizes (Prestwich et al, 2014a). The lack of stronger effects for theory-based interventions may be due issues around poor reporting of theory, poor application of theory or just poor theories (Prestwich et al, 2015); future research should therefore be mindful of such issues.…”
Section: Future Directions For Research On Health Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increased recognition of the need for systematic and extensive application of theory to the design of interventions [18,[55][56][57][58][59]; this is reflected, for example, in the UK Medical Research Council's framework for designing and evaluating complex interventions [21] and the Intervention Mapping framework [60] for planning health promotion programmes.…”
Section: Behaviour Change Theory: Specifying the Mechanisms Of Actionmentioning
confidence: 99%